Key attributes of nitrocellulose-based energetic materials and recent developments - Khoirul Solehah Abdul Rahim; Alinda Samsuri; Siti Hasnawati Jamal; Siti Aminah Mohd Nor; Siti Nor Ain Rusly; Hafizah Ariff; Nur Shazwani Abdul Latif (Heliyon)
Nitrocellulose (NC)-based propellants have played a pivotal role in the development of energetic materials for both military and civilian applications. This review offers a comprehensive exploration of NC-based propellants, tracing their evolution from their historical origins as smokeless gunpowder to modern advancements. It discusses the chemical composition and classifications of NC propellants, along with continuous efforts to refine smokeless powder formulations through studies on smoke formation, residues, and additives. Modern techniques such as PCR-based detection and dynamic light scattering have enabled precise analysis of NC properties, including variations in the degree of substitution and molar mass, which allow for tailoring the chemical structure to meet specific performance needs. Special attention is given to the combustion dynamics of NC-based propellants, with an emphasis on reaction zones, performance characteristics, and optimization strategies that enhance their overall efficacy. The review also highlights the significant impact of nitrogen content, additives, and processing methods on the performance, stability, and safety of NC-infused propellants. While higher nitrogen content improves energetic output, it also increases surface cracking and gas production, necessitating the use of stabilizers and additives like Bu-NENA, copper compounds, and MgH2 to enhance flexibility, thermal stability, and reduce sensitivity to mechanical and thermal stimuli. Aging and environmental factors further influence burn rate variation, underscoring the need for tailored formulations. In terms of environmental sustainability, this review addresses safety considerations in handling and disposing of NC-based materials, focusing on innovations such as alkaline hydrolysis and NC recovery to mitigate environmental risks. Stabilizers and eco-friendly additives effectively prevent chemical degradation, reduce shock sensitivity, and enhance thermal stability. The review concludes with future research directions aimed at further improving the stability and safety of NC-based propellants, ensuring their continued relevance in modern applications.